Translational offsetting as a mode of estrogen receptor α‐dependent regulation of gene expression. (26th September 2019) - Lorent, Julie; Kusnadi, Eric P; van Hoef, Vincent; Rebello, Richard J; Leibovitch, Matthew; Ristau, Johannes; Chen, Shan; Lawrence, Mitchell G; Szkop, Krzysztof J; Samreen, Baila; Balanathan, Preetika; Rapino, Francesca; et al.
Abstract: Estrogen receptor alpha (ERα) activity is associated with increased cancer cell proliferation. Studies aiming to understand the impact of ERα on cancer‐associated phenotypes have largely been limited to its transcriptional activity. Herein, we demonstrate that ERα coordinates its transcriptional output with selective modulation of mRNA translation. Importantly, translational perturbations caused by depletion of ERα largely manifest as "translational offsetting" of the transcriptome, whereby amounts of translated mRNAs and corresponding protein levels are maintained constant despite changes in mRNA abundance. Transcripts whose levels, but not polysome association, are reduced following ERα depletion lack features which limit translation efficiency including structured 5′UTRs and miRNA target sites. In contrast, mRNAs induced upon ERα depletion whose polysome association remains unaltered are enriched in codons requiring U34‐modified tRNAs for efficient decoding. Consistently, ERα regulates levels of U34‐modifying enzymes and thereby controls levels of U34‐modified tRNAs. These findings unravel a hitherto unprecedented mechanism of ERα‐dependent orchestration of transcriptional and translational programs that may be a pervasive mechanism of proteome maintenance in hormone‐dependent cancers. Synopsis: ERα suppression reprograms epithelial cells via selective changes in transcription and translation. Surprisingly, a subset of mRNAs with ERα‐dependent transcription is not translated congruently, a phenomenon we termed translational offsetting. A subset of transcripts with alterations in their steady‐state levels following ERα perturbation and/or activity are offset at the level of translation. Transcripts undergoing translational offsetting share features in their 5′ untranslated region or require a subset of modified tRNAs for their translation. ERα regulates the expression of tRNA modification enzymes, whereby U34 tRNA modifications play a major role in translational offsetting. Abstract : In addition to its well‐established role in transcription, ERα also modulates levels of translation of selective transcripts that show alteration in their steady‐state levels following ERα perturbation, a phenomenon referred to as translational offsetting.